Aortic Valve Thrombosis in Antiphospholipid Syndrome Causing Coronary Artery Embolic Disease - Burt, Jeremy R; Beavers, Kimberly M; Grekoski, Vincent E (Journal of Cardiovascular Medicine and Cardiology, 2016)
Antiphospholipid syndrome (APS) is a disorder characterized by the presence of antiphospholipid antibodies which are known to promote thrombus formation and heart valve complications. In this case, a 20 year old African American male presenting with chest pain was found to have APS as well as Budd-Chiari Syndrome. He was then evaluated through the use of cardiac magnetic resonance imaging and cardiac catheterization, which revealed an aortic valve thrombus as well as myocardial infarction from coronary artery emboli. This is the first time this condition has been documented in the literature and serves as an example of successful detection and treatment. The patient underwent coronary artery bypass grafting and the thrombus was surgically removed. The patient was discharged with lifelong prescription for anticoagulant medication.